Mid‐infrared supercontinuum covering 2.0–16 μm in a low‐loss telluride single‐mode fiber (Laser Photonics Rev. 11(2)/2017). Issue 2 (March 2017) - Zhao, Zheming; Wu, Bo; Wang, Xunsi; Pan, Zhanghao; Liu, Zijun; Zhang, Peiqing; Shen, Xiang; Nie, Qiuhua; Dai, Shixun; Wang, Rongping
Abstract : A mid‐infrared (MIR) supercontinuum (2–16 μm @40 dB) has been generated in a telluride glass fiber, which covers the whole MIR molecular fringerprint region, as this is of key importance for extensive applications in diagnostics, gas sensing, and greenhouse CO2 detection. It is also a fresh demonstration of the single‐mode telluride glass fiber for its merits of ultra‐high nonlinearity and low‐loss. (Picture: Zheming Zhao et al., article number 1700005, in this issue)